Towards Utilization of Neurofuzzy Systems for Taxonomic Identification Using Psittacines as a Case Study. (21st February 2016) - Rahimi, Shahram; Spiess, Cynthia R.; Gupta, Bidyut; Sahebkar, Elham
Abstract : Demonstration of the neurofuzzy application to the task of psittacine (parrot) taxonomic identification is presented in this paper. In this work, NEFCLASS-J neurofuzzy system is utilized for classification of parrot data for 141 and 183 groupings, using 68 feature points or qualities. The reported results display classification accuracies of above 95%, which is strongly tied to the setting of certain parameters of the neurofuzzy system. Rule base sizes were in the range of 1, 750 to 1, 950 rules.